Emily Wilson’s Translations of The Iliad and The Odyssey, and Walter J. Ong’s Thought - Farrell, Thomas J. (New Explorations)

(untitled) (New Explorations Association, 2024)
In the first part of my article, I highlight the work of the American Jesuit Renaissance specialist and cultural historian and pioneering media ecology theorist Walter J. Ong (1912-2003; Ph.D. in English, Harvard University, 1955) of Saint Louis University. In the second part, I discuss the classicist Emily Wilson’s translations of The Odyssey (2018) and The Iliad (2023).